Growth of off-flavours-caused phytoplankton in milkfish culture fertilized with different N:P - Azis, Rahmadi; Affandi, Ridwan; Nirmala, Kukuh; Prihadi, Triheru (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT Milkfish culture in ponds currently use inorganic fertilizers for growing phytoplankton. Giving of urea and SP (superphosphate) too much in the pond environment will cause eutrophication and often cause fish smell of mud (off-flavours). Off-flavours in fish is caused by two chemical compounds those are geosmin and 2-methylisoborneol (MIB). Research was performed to evaluate the growth of off-flavours-caused phytoplankton in milkfish culture fertilized by different N:P. This study used nine ponds. Ponds are used for fish rearing area of 600 m2. Fish reared in ponds at the density of 1 fish/m2 for 90 days. The study were showed that types of phytoplankton obtained were the phylum Chlorophyta, Cyanophyta, Bacillariophyta, Dinoflagellate, Glaocophyta, and Euglenophyta. Percentage abundance of phytoplankton that produced geosmin and MIB (Cyanophyta) in each treatment was less than 50% of the percentage of total phytoplankton. Organoleptic scores showed that the treatment pond G (N:P ratio 4) score of 7 (not fresh, no off-flavours). Organoleptic scores of treatments with N:P ratio 5, 15 and 30 in pond A (freshwater pond) and pond B (brackish water pond) were 8 (fresh, no off-flavours). Keywords: extensive pond-culture, phytoplankton, N:P ratio, organoleptic ABSTRAK Budidaya bandeng di tambak saat ini menggunakan pupuk anorganik untuk menumbuhkan fitoplankton. Pemberian pupuk urea dan SP (superphosphate) yang berlebihan pada lingkungan budidaya akan menyebabkan kondisi perairan tersebut menjadi sangat subur dan sering menyebabkan ikan bau lumpur off-flavours. Bau lumpur di ikan disebabkan oleh dua senyawa kimia yaitu geosmin dan 2-methylisoborneol (MIB). Penelitian dilakukan untuk menguji pertumbuhan fitoplankton penyebab bau lumpur pada tambak ikan bandeng dipupuk dengan N:P berbeda. Penelitian ini menggunakan sembilan petak tambak. Tambak yang digunakan berukuran 600 m2. Ikan ditebar di tambak dengan kepadatan 1 ikan/m2 dan dipelihara selama 90 hari. Hasil penelitian menunjukkan fitoplankton yang didapatkan antara lain berasal dari filum Chlorophyta, Cyanophyta, Bacillariophyta, Dinoflagellata, Glaocophyta, dan Euglenophyta. Kelimpahan fitoplankton Cyanophyta lebih kecil dibandingkan dengan fitoplankton bukan Cyanophyta yaitu di bawah 50%. Skor organoleptik perlakuan tambak G (rasio N:P 4) yaitu 7 (kurang segar, tidak bau lumpur). Skor organoleptik perlakuan rasio N:P 5, 15, dan 30 di tambak A (tambak air tawar) dan tambak B (tambak air payau) adalah 8 (segar, tidak bau lumpur). Kata kunci: budidaya kolam ekstensif, fitoplankton, rasio N:P, organoleptik